Gene polymorphism of blood coagulation factors and endothelial dysfunction in early and late preeclampsia. - T. O. Loskutova; T. V. Demchenko; N. V. Kryachkova (Medičnì Perspektivi)
The aim of our study was to find out the influence of gene polymorphisms of coagulation factors, endothelial dysfunction and regulators of blood pressure in early (EPE) and late preeclampsia (LPE). The study of genetic polymorphisms of blood coagulation factors and fibrinolysis (1691 G/A factor V Leiden (FVL), 20210 G/A prothrombin, -675 5G/4G PAI-1, 455 G/A fibrinogen β), endothelial dysfunction (192 Q → R paraoxonase 1, 677 C/T MTHFR, arterial pressure regulator (235 M/T angiotensinogen II (AGT II)) using an PCR was performed. A prospective cohort study of 39 women with EPE, 93 with LPE and 44 pregnant women with a physiological pregnancy (C group) was conducted. The average gestational age at the time of delivery in EPE group was lower than in LPE and control group (p<0.001). In group with EPE new-borns had low weight-growth characteristics, low grade by the Apgar scale and foetal distress (38.5% vs. 9.7%, p<0.05). Caesarean section in EPE group was performed by 2.25 times more often than in control group and by 2,13 times than in LPE group (p<0,05). It was detected that the number of 1691 GA FVL heterozygote carriers in the group with EPE was significantly higher than in LPE group (p<0.05, OR=3.65, 95% CI 1.5-8.9) and control group (6.04, 1.7-21.6). The number of 20210 GG homozygotes and 20210 GA heterozygotes in prothrombin gene was probably lower in EPE group compared with the LPE and control group (0.03, 0.002-0.49, and 0.18, 0.06-0.53, respectively). It was established increase in frequency of 677 TT MTHFR genotype in EPE compared with control group (17.27; 0.9-317). Also, the carriers of 235T allele AGT II gene have an increased risk of EPE and PPE development (2.25, 1.2-4.2), (1.9, 1.1-3.3) respectively. The allele -455A of fibrinogen β gene increases the chances of developing EPE by 4.4 times (2.0-9.5), and LPE by 3.5 times (1.7-7.1). Risk factors that significantly increase the chances of developing early preeclampsia were identified: allele 1691 A of FV Leiden (5.96, 1.5-8.9), allele 20210 A of prothrombin (39.8, 2,3-679), 677T MTHFR (2.5, 1.18-5.3). In was detected that other researched polymorphisms between groups with PE were not significantly different and did not affect on time of preeclampsia development.